The dynamic equilibrium between population aging and the allocation of elderly medical care resources in the Yellow River Basin - Long Hai; Yanghao Cui; Jiawei Zhang; Rui Wang (BMC Public Health)
Abstract Background Population aging, as a global issue, has garnered significant attention worldwide. The rational allocation of elderly healthcare resources is critical to addressing this challenge. This study investigates the spatiotemporal evolution of population aging in the Yellow River Basin and evaluates the equilibrium between aging demographics and healthcare resource distribution. Methods This paper uses the Dagum Gini coefficient decomposition method to analyze regional differences and the dynamic evolution process of population aging in various provinces of the Yellow River Basin. The entropy method is employed to evaluate the elderly care and medical resource allocation in the provinces of the Yellow River Basin in 2020. By combining geographical concentration and the inconsistency index, the study investigates the matching relationship and distribution characteristics between aging levels and elderly care medical resource allocation. Results The level of aging in the provinces of the Yellow River Basin has been deepening, showing a stepwise increase from west to east. The spatial imbalance in aging, as measured by the Dagum Gini coefficient, decreased from 0.126 in 2000 to 0.099 in 2020. However, the contribution rate of intra-regional differences rose from 23.096% to 40.487%, making it the primary source of disparity. The core provinces (Shandong, Henan, Sichuan) had comprehensive scores of 0.946, 0.846, and 0.793, respectively, while the peripheral provinces (Qinghai, Gansu, Ningxia) scored only 0.001, 0.226, and 0.012. A positive correlation was found between the elderly population and elderly healthcare resources, but 55.56% of the provinces exhibited either resource lag (RI > 1) or over-allocation (RI < 0.8), indicating a mismatch. Conclusion The Yellow River Basin displays marked spatiotemporal heterogeneity in aging and resource distribution. Most provinces exhibit incoordinate matching relationships, characterized by insufficient supply or low utilization efficiency. Provincial authorities should implement region-specific policies, optimizing resource allocation and tailoring strategies to local demographic-geographic conditions.